Agricultural commercialization, nutrition, and the rural poor - Bouis, Howarth E.; Haddad, Lawrence James (Lynne Rienner Publishers, 1990)
The authors investigate who, how, and why some benefit from the process of agricultural commercialization while others lose, drawing on a wide range of information at the household and individual level collected from a random sample of 500 households in the Philippines.